2020
DOI: 10.3389/fpsyg.2020.614660
|View full text |Cite
|
Sign up to set email alerts
|

Trait Procrastination and Mobile Phone Addiction Among Chinese College Students: A Moderated Mediation Model of Stress and Gender

Abstract: Recent studies have indicated that trait procrastination as a personality factor could lead to mobile phone addiction, however little is known about the mediating and moderating mechanisms underlying this process. The current study investigated the mediating role of stress in the relationship between trait procrastination and mobile phone addiction, and whether the mediating effect was moderated by gender. A sample including 1,004 Chinese college students completed measurements of trait procrastination, stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 54 publications
(85 reference statements)
3
50
0
2
Order By: Relevance
“…The influence of perceived stress on smartphone addiction has begun to gain empirical support ( Chiu, 2014 ; Yang et al, 2020 ). However, questions concerning the underlying mediating and moderating mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of perceived stress on smartphone addiction has begun to gain empirical support ( Chiu, 2014 ; Yang et al, 2020 ). However, questions concerning the underlying mediating and moderating mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Medical college students, as a special group of college students, have high levels of stress that could be due to academic burden, frequency of examinations, lengthy academic curriculum, and worrying about the future ( Gazzaz et al, 2018 ). When faced with this stress, they are more likely to use smartphones as a way to relieve stress ( Yang et al, 2020 ). Perceived stress refers to the degree to which an individual perceives an external event as stress ( Cohen et al, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that bedtime procrastination played a mediating effect in the positive correlation between PMPU and sleep quality in Chinese college students [53]. In addition, studies have also found that trait procrastination and general procrastination may lead to PMPU [54,55]. From personality trait theory we know that personality affects behavior [56]; bedtime procrastination, as a characteristic of the procrastinating personality, may then also affect PMPU, but no research has focused on this possible relationship.…”
Section: Bedtime Procrastinationmentioning
confidence: 99%
“…Similar smartphone behavioral patterns were found in medical college students, where females were more likely to use multiple media applications while males used game apps [ 32 ]. Moreover, gender was reported as moderating smartphone addiction and the perfectionism trait: males with a higher tendency of perfectionism have a higher risk of addiction to smartphone use [ 37 ], and the procrastination trait was correlated with smartphone addiction in both gender groups [ 38 ].…”
Section: Introductionmentioning
confidence: 99%